2010
DOI: 10.1002/j.1839-4655.2010.tb00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Change and Adaptation in Families with Young Carers

Abstract: Using grounded theory methodology, members of nine families with 'young carers' were interviewed to explore their experiences of caring. A dynamic theory of change and adaptation emerged in relation to changes in who cares within families, in external support and in the attitudes of young carers towards caring. Adaptations included becoming used to the way life is, knowing how to care, balancing and trading off, rewarding care, and anticipating future adaptations. A model has been developed to offer an explana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Our study reveals that responsibility for providing developmental space often rests on adults, who endeavour to maintain a balance between caring responsibilities and having a normal life for themselves and their children. This is consistent with McDonalds’ finding that “balancing and trading off” is a significant strategy that parents use to ensure that each family member's needs are met (McDonald, Dew, & Cumming, ). Our study suggests that for young carers, school is an important “carefree island” that enables them to maintain their own developmental space.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study reveals that responsibility for providing developmental space often rests on adults, who endeavour to maintain a balance between caring responsibilities and having a normal life for themselves and their children. This is consistent with McDonalds’ finding that “balancing and trading off” is a significant strategy that parents use to ensure that each family member's needs are met (McDonald, Dew, & Cumming, ). Our study suggests that for young carers, school is an important “carefree island” that enables them to maintain their own developmental space.…”
Section: Discussionsupporting
confidence: 83%
“…McDonalds' finding that "balancing and trading off" is a significant strategy that parents use to ensure that each family member's needs are met (McDonald, Dew, & Cumming, 2010). Our study suggests that for young carers, school is an important "carefree island" that enables them to maintain their own developmental space.…”
Section: Discussionmentioning
confidence: 76%
“…This may suggest that doing it for longer (as a function of being older) makes acts of compassion less noticeable and less unique with time. This finding was complemented by McDonald et al ( 2010 ) who found that for some YCs, caregiving became a natural behaviour, and with time, both parents and children have gotten used to it. However, it should be noted that habituating to the caregiving role could just be a function of how they have entered the role and the length of time they care for.…”
Section: Discussionmentioning
confidence: 90%
“…However, it should be noted that habituating to the caregiving role could just be a function of how they have entered the role and the length of time they care for. In other words, those who reported it was normal for them could have been socialized into the role (e.g., have been born into it), and since they started caregiving at an earlier age, it was all they knew (Hamilton & Adamson, 2013 ; McDonald et al, 2010 ; Smyth et al, 2011a , 2011b ). The ability to provide caregiving “naturally” could also indicate temperamental differences that other children and youth may not possess (Lakman & Chalmers, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…By providing most of the care, the parents reduce their children's caring responsibilities, which may still be substantial (taking up to 3 h per day in this study). Parents try to maintain a balance between their children's caring responsibilities and being “normal kids” in an attempt to ensure that each family member's needs are met (McDonald et al, 2010; Nagl‐Cupal & Hauprich, 2018). Overcoming these challenges requires family cohesion, problem‐solving skills, and educational competencies within the family (De Jong & Schout, 2013; Schout et al, 2017), as well as strong family bonds facilitated by family routines, rituals, and shared time, in addition to recreation (Black & Lobo, 2008), all of which were frequently illustrated in this study.…”
Section: Discussionmentioning
confidence: 99%